Preparatory Control Against Distraction Is Not Feature-Based. (29th September 2021) - Liesefeld, Heinrich R; Liesefeld, Anna M; Müller, Hermann J
Abstract: Salient-but-irrelevant stimuli (distractors) co-occurring with search targets can capture attention against the observer's will. Recently, evidence has accumulated that preparatory control can prevent this misguidance of spatial attention in predictable situations. However, the underlying mechanisms have remained elusive. Most pertinent theories assume that attention is guided by specific features. This widespread theoretical claim provides several strong predictions with regard to distractor handling that are disconfirmed here: Employing electrophysiological markers of covert attentional dynamics, in three experiments, we show that distractors standing out by a feature that is categorically different from the target consistently captures attention. However, equally salient distractors standing out in a different feature dimension are effectively down-weighted, even if unpredictably swapping their defining feature with the target. This shows that preparing for a distractor's feature is neither necessary nor sufficient for successful avoidance of attentional capture. Rather, capture is prevented by preparing for the distractor's feature dimension.